Isolated cleft palate requires different surgical protocols depending on cleft type. Issue 4 (4th July 2017) - Elander, Anna; Persson, Christina; Lilja, Jan; Mark, Hans
Abstract: A staged protocol for isolated cleft palate (CPO), comprising the early repair of the soft palate at 6 months and delayed repair of the eventual cleft in the hard palate until 4 years, designed to improve maxillary growth, was introduced. CPO is frequently associated with additional congenital conditions. The study evaluates this surgical protocol for clefts in the soft palate (CPS) and for clefts in the hard and soft palate (CPH), with or without additional malformation, regarding primary and secondary surgical interventions needed for cleft closure and for correction of velopharyngeal insufficiency until 10 years of age. Of 94 consecutive children with CPO, divided into four groups with (+) or without (−) additional malformations (CPS + or CPS − and CPH + or CPH−), hard palate repair was required in 53%, performed with small local flaps in 21% and with bilateral mucoperiosteal flaps in 32%. The total incidence of soft palate re-repair was 2% and the fistula repair of the hard palate was 5%. The total incidence of secondary velopharyngeal surgery was 17% until 10 years, varying from 0% for CPS − and 15% for CPH−, to 28% for CPS + and 30% for CPH+. The described staged protocol for repair of CPO is found to be safe in terms of perioperative surgical results, with comparatively low need for secondary interventions. Furthermore, the study indicates that the presence of a cleft in the hard palate and/or additional conditions have a negative impact on the development of the velopharyngeal function.